GRAMMATICAL CHANGES IN SENSE AND SENIBILITY (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract. The article discusses the grammatical changes and the factors that cause them in Sense and Sensibility by Jane Austin. Also, during this analysis, as a result of comparing the work with the version in Uzbek language, examples of grammatical changes are given below.